2009
DOI: 10.1063/1.3068194
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rise of a liquid into a deformable porous material

Abstract: We examine the effects of capillarity and gravity in a model of one-dimensional imbibition of an incompressible liquid into a deformable porous material. We focus primarily on a capillary rise problem but also discuss a capillary/gravitational drainage configuration in which capillary and gravity forces act in the same direction. Models in both cases can be formulated as nonlinear free-boundary problems. In the capillary rise problem, we identify time-dependent solutions numerically and compare them in the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 42 publications
3
51
0
Order By: Relevance
“…sap flow, spore release), and it is of fundamental and practical importance to estimate the time to reach equilibrium in such systems, as well as to understand their transient dynamics. Recent examples of such elastocapillary dynamics include studies of capillary-driven flow in deformable porous media (Siddique et al 2009) and in flexible channels where gravitational effects could be neglected (van Honschoten et al 2007;Aristoff et al 2010). Here, we consider a model system to study elastocapillary dynamics with gravity, namely capillary rise between flexible sheets that are clamped at their upper ends.…”
Section: Introductionmentioning
confidence: 99%
“…sap flow, spore release), and it is of fundamental and practical importance to estimate the time to reach equilibrium in such systems, as well as to understand their transient dynamics. Recent examples of such elastocapillary dynamics include studies of capillary-driven flow in deformable porous media (Siddique et al 2009) and in flexible channels where gravitational effects could be neglected (van Honschoten et al 2007;Aristoff et al 2010). Here, we consider a model system to study elastocapillary dynamics with gravity, namely capillary rise between flexible sheets that are clamped at their upper ends.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of gravity effects, in the beginning both curves follow similarity solution and then deviate from this trend and reach to equilibrium solution. The limit of this presentation of these graphical results is up to this and readers are referred to Siddiqui et al [20] for more details where steady state solution along with experimental comparison can be found. Anderson [29] also studied the imbibition of a liquid droplet on a deformable porous substrate using mixture theory approach.…”
Section: Unidirectional Capillary Rise Into Deformable Porous Materialsmentioning
confidence: 99%
“…In their model the gravity effects were not present and it is reported that imbibition of liquid into deformable porous material results into swelling, swelling relaxation, and shrinking. Later on, Siddique et al [19,20,30] studied the capillary rise phenomena into a deformable sponge like material by including the gravity, power law and MHD fluid effects. On the similar lines, Sommer and Mortensen [31] studied unidirectional forced infiltration in an initially dry sponge like material.…”
Section: Unidirectional Capillary Rise Into Deformable Porous Materialsmentioning
confidence: 99%
See 2 more Smart Citations